A new species of Amphinemura (Plecoptera: Nemouridae) from Vietnam, with additions to A. bimaculata Li, Wang and Yang, 2016 - Yan, Yanhua; Wang, Ying; Yang, Ding; Li, Weihai (Zootaxa, 2021)
A new species of the Amphinemurinae genus Amphinemura, A. similibimaculata sp. nov. is described from central Vietnam. The new species is compared with related congeneric Amphinemura bimaculata Li, Wang and Yang, 2016. Taxonomic notes on A. bimaculata are also presented.